Jabuticaba as a Source of Functional Pigments - T. Santos, Diego; A. Meireles, M. Angela (Pharmacognosy Reviews)
The relatively high concentration of anthocyanins in the diet is of prospective importance to human health. Anthocyanins contribute greatly to the antioxidant properties of certain colorful foods, such as grapes and cranberries. Many studies in recent years have focused on the study of these functional pigments from different perspectives. The present review highlights recent studies on the health-promoting properties of anthocyanins. It presents latent anthocyanin sources and demonstrates the potentiality of an under-utilized non-conventional source widespread in Brazil called jabuticaba (Myrciaria cauliflora).
Keywords: Anthocyanins; functional pigments; health-promoting properties; jabuticaba